1981
DOI: 10.1002/1097-0142(19810301)47:5<906::aid-cncr2820470516>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Hemangiopericytoma: A light microscopic and ultrastructural study

Abstract: An ultrastructural study of three cases of hemangiopericytoma showed cells partially or completely enveloped by well-formed basement membrane and basement membrane-like material. The cells exhibited prominent cytoplasmic filaments, some showing dense body formation, interdigitating cytoplasmic processes, and pinocytotic vesicles. A review of the literature revealed only 19 other cases of hemangiopericytoma studied by electron microscopy, and these included seven cases of meningeal origin ("angioblastic meningi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(33 citation statements)
references
References 20 publications
1
32
0
Order By: Relevance
“…2 12 Eichorn et al and Batsakis et al showed no distinction between the ultrastructural findings of nasal hemangiopericytomas and those of other sites. The tumor must be differentiated from other vascular tumors, fibrous histiocytomas, smooth muscle tumors, and soft tissue sarcomas by subtle histologic features, Reticulin stains are helpful in defining the vascular spaces; in hemangiopericytomas, this stain will display the perivascular growth of pericytes in contrast to the intravascular growth of hemangioendothelioma cells.…”
Section: Discussionmentioning
confidence: 97%
“…2 12 Eichorn et al and Batsakis et al showed no distinction between the ultrastructural findings of nasal hemangiopericytomas and those of other sites. The tumor must be differentiated from other vascular tumors, fibrous histiocytomas, smooth muscle tumors, and soft tissue sarcomas by subtle histologic features, Reticulin stains are helpful in defining the vascular spaces; in hemangiopericytomas, this stain will display the perivascular growth of pericytes in contrast to the intravascular growth of hemangioendothelioma cells.…”
Section: Discussionmentioning
confidence: 97%
“…9,10 According to findings from several studies, radiotherapy is an effective treatment for intracranial haemangiopericytoma. These tumours comprise <2.5% of meningeal tumours and <1% of all intracranial tumours.…”
Section: Discussionmentioning
confidence: 99%
“…This lesion was thought to fall in the spectrum between glomus tumors and capillary hemangioma, and hence the term hemangiopericytoma was chosen. 10 Compagno and Hyams 3 described these lesions as intranasal hemangiopericytoma tumors. It is now widely accepted as a type of so-called sinonasal hemangiopericytoma, now known as glomangiopericytoma, which is different from the traditional soft-tissue hemangiopericytoma rep-resenting as a separate lesion.…”
Section: Discussionmentioning
confidence: 99%